Investigation of Aggravating Psychosocial Factors on Health and Predictability of Smoking and Alcohol Use in Post Adolescent Students - Barmpagianni, Effrosyni (Health Psychol Res, 2013)
Purpose of this study is to explore those factors which affect the health of students in postadolescent age, focusing on smoking and alcohol use, especially in regard to ways of predicting adoption of this behavior and its frequency to detect future users of tobacco and alcohol use but also high-risk groups, i.e. those people who are led to abuses. On the basis of the research part is the Theory of Planned Behaviour, the axes of which are to be investigated. Specifically, the factors evaluated, except for population parameters, behavioral attitudes, i.e. attitudes towards the behavior of tobacco use and alcohol regulations subjective perceptions and perceptions of control, perceived behavioral control and self-efficacy. Intention is explored to continue or start using tobacco and alcohol in the future and evaluate the behavior. The sample consisted of 138 students of postadolescent age, 18-25 years of both sexes, all of the University of Peloponnese and the Technological Educational Institute of Kalamata, Department of Sparta, Greece. The results of a series of statistical analysis, via SPSS 21.0 statistical program revealed the predictive power of perceived behavioral control and subjective norms to the intention of interpreting 64% of the variance of the latter, of the attitudes toward alcohol in relation to intention that interpret 69% of the variance, of the normative beliefs toward smoking with 69% range of interpretation to the dependent variable, of the perceived behavioral control of smoking with 72% and of the attitudes toward smoking with 77% of interpretation. The results demonstrate the significance and application in universities and technological educational institutes appropriate primary preventive interventions for students nonusers of tobacco and alcohol and appropriate programs of secondary and tertiary prevention in heavy users of tobacco and alcohol use and high-risk individual.